Relationship between Exclusive Breastfeeding and Nutritional Status of Infants Aged 12 months - Sheilla Selvina; Eddy Fadlyana; Nita Arisanti (Althea Medical Journal, 2015)
Background: Exclusive breastfeeding has a high nutrient content to fulfill the nutritional needs of infants aged 0−6 months. The aim of this study was to describe thenutritional status of infants aged 12 months and to determine the relationship of exclusive breastfeeding and nutritional status of infants aged 12 months in Pos Pelayanan Terpadu (Posyandu) Cipacing Village Jatinangor.Methods: A cross sectional study was carried out to 102 mothers with infants aged 12 months in Posyandu Cipacing Village from September to October 2013. The infants’ body weight were weighed with weight scales which had been calibrated and the body length were measured with the Seca 210 baby length measuring mat, then the mother was interviewed with a questionnaire which had been validated to inquire about the exclusive breastfeeding history. The Fisher exact test was used to assess relationship between both variables.Results: There were 81.3% of infants with good nutritional status and 83.3% of infants who did not get exclusive breastfeeding. The analysis test showed that the p-value of relationship between exclusive breastfeeding and nutritional status was 0.458 with odds ratio 3.343.Conclusions: Most of the infants are in good nutritional status although they do not get exclusive breastfeeding. Consequently, there is not a significant relationship between exclusive breastfeeding and nutritional status. [AMJ.2015;2(4):534–40] DOI: 10.15850/amj.v2n4.638